Mimicking the brain: Epstein-Barr virus and foreign agents as drivers of neuroimmune attack in multiple sclerosis - Thomas, Olivia G.; Olsson, Tomas (Frontiers in Immunology, 2023)
T cells have an essential role in adaptive immunity against pathogens and cancer, but failure of thymic tolerance mechanisms can instead lead to escape of T cells with the ability to attack host tissues. Multiple sclerosis (MS) occurs when structures such as myelin and neurons in the central nervous system (CNS) are the target of autoreactive immune responses, resulting in lesions in the brain and spinal cord which cause varied and episodic neurological deficits. A role for autoreactive T cell and antibody responses in MS is likely, and mounting evidence implicates Epstein-Barr virus (EBV) in disease mechanisms. In this review we discuss antigen specificity of T cells involved in development and progression of MS. We examine the current evidence that these T cells can target multiple antigens such as those from pathogens including EBV and briefly describe other mechanisms through which viruses could affect disease. Unravelling the complexity of the autoantigen T cell repertoire is essential for understanding key events in the development and progression of MS, with wider implications for development of future therapies.